Sinergitas Stakeholder dalam Pengelolaan Limbah Industri untuk Mewujudkan Lingkungan Berkelanjutan di Kabupaten Sidoarjo - Rahmawati, Lutfia Diva; Puspaningtyas, Anggraeny; Wahyudi, Eddy (Public Administration Dept, Faculty of Social and Political Science, 2025)
Sidoarjo Regency is one of the regions with the highest number of industries in East Java. This condition makes Sidoarjo prone to environmental pollution, particularly caused by industrial waste that is not managed optimally. This study aims to analyze stakeholder synergy in industrial waste management as an effort to achieve environmental sustainability in Sidoarjo Regency. The approach used is descriptive qualitative, applying the stakeholder synergy theory by Satibi and Vaugan, which consists of five dimensions: shared perception, communication patterns, policy actors' attitudes, organizational structure, and resource potential. Data were collected through in-depth interviews, documentation, and analysis of relevant secondary data. The results of the study show that stakeholder synergy has been initiated but is not yet functioning optimally. In the dimension of shared perception, there are still differences in understanding among parties regarding technical regulations and authority distribution. Communication between institutions tends to be incidental and unstructured, while outreach to the public remains limited. The attitude of policy actors shows commitment and responsiveness, but this has not yet been followed by consistent policy implementation. The organizational structure between institutions has been established, but it has not been fully integrated into a collaborative working system. Meanwhile, the potential of available resources—particularly human resources and monitoring facilities remains limited and has not been able to cover all areas affected by industrial waste.